2017
DOI: 10.1590/1983-40632016v4742790
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, phenometric and productive changes in soybean crop due to the use of kinetin

Abstract: A fast growth in the use of substances that increase soybean yield through physiological or morphological changes, such as cytokinin, has taken place in recent years. This study aimed at assessing the effect of the application time of cytokinin as kinetin on soybean crops. The experiment was carried out under field conditions, using four treatments (control and kinetin at the vegetative stages V4, V6 and V4 + V6), with five replications, in completely randomized blocks. Physiological (nitrate reductase and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(16 reference statements)
0
8
0
1
Order By: Relevance
“…Also, the level of auxin and cytokinin decides the NR-ase activity in crops. Soares et al [18] reported that increased cytokinin synthesis promoted nitrate reductase activity in soybean. Increased auxin content also promotes nitrate reductase enzyme production according to Anbarasu [19]…”
Section: Nitrate Reductasementioning
confidence: 99%
“…Also, the level of auxin and cytokinin decides the NR-ase activity in crops. Soares et al [18] reported that increased cytokinin synthesis promoted nitrate reductase activity in soybean. Increased auxin content also promotes nitrate reductase enzyme production according to Anbarasu [19]…”
Section: Nitrate Reductasementioning
confidence: 99%
“…al, (2008) trabalhando com Annona glabra citam o efeito a citocinina aplicada em áreas foliares no aumento da quantidade de clorofila e cloroplastos. Soares et al (2017) aplicaram citocinina em plantas de Glycinemax relatam o aumento dos níveis da enzima nitrato redutase e aumento da eficiência de absorção de nitrogênio. Esses incrementos podem explicar o aumento na matéria seca por permitir a planta de pitaia o maior acúmulo de esqueletos de carbono.…”
Section: Massa Seca Das Brotaçõesunclassified
“…The average reduction of 35.92% verified in the minimum points for the leakage of electrolytes, represents the maintenance of the integrity of the cellular membranes. The cytokinins maintain cell membrane integrity, through the balance between cytokinin and abscisic acid (Fioreze, Rodrigues, Carneiro, Silva, & Lima, 2013), preventing the transport of proteases from the vacuole to the cytoplasm, hydrolyzing soluble proteins of plasma membranes, chloroplasts, and mitochondria, blocking the oxidation of fatty acids and inhibiting the formation and degradation of free radicals (Soares et al, 2017).…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…The application of biostimulants containing cytokinin or the isolated use of the growth regulator, via foliar applications, has shown a strong tendency to increase the yield of soybean crop (Soares, Dourado Neto, Fagan, Teixeira, & Pereira, 2017). Borges, Torres Junior, Neves, Cruvinel, Santos, and Matos (2014), when applying N6-benzyladenine (6-BA) at the end of soybean flowering, found a reduction of pod abortion, and an increase of stem diameter, the yield of components and the crop.…”
Section: Introduce the Problemmentioning
confidence: 99%